COMPLEMENTARY FEEDING, PECULIARITIES OF INTRODUCTION. CLINICAL CASES - Vera A. Skvortsova; Tatiana E. Borovik; Tatiana V. Bushueva; Natalia G. Zvonkova; Olga L. Lukoyanova; Elena A. Roslavtseva; Irina M. Guseva ("Paediatrician" Publishers LLC, 2017)
The article presents modern, scientifically substantiated approaches to the introduction of complementary feeding in healthy breastfed infants as well as in infants with overweight and various diseases - atopic dermatitis (food allergy), protein-energy deficiency in the context of chronic cardiovascular insufficiency syndrome, neurological disorders, celiac disease. The peculiarities of various complementary foods are demonstrated in clinical examples.